Kinerja Dan Kompensasi Masa Depan Di Bank Syariah Dan Konvensional - Evy Rahman Utami (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2017)
The objective of this study is to examine the relationship between changes of performance and changes of compensation of board commissioners and board of directors. In contrast to previous research, this study compare the relationship on conventional banking and Islamic banking in Indonesia. The samples of this research are conventional and Islamic banking between periode 2011-2015. Data in this study were obtained from financial statements. Regression analysis will be employed to answer the research questions. The result showed that there is a positive relationship between changes of performance and compensation. However, there is no difference the relationship of performance and compensation on the conventional and Islamic banking. This study supported the agency theory, but it does not support the stewardship theory.